Handling effective communication to support awareness in rescue operations. (29th September 2020) - Chehade, Samer; Matta, Nada; Pothin, Jean‐Baptiste; Cogranne, Remi
Abstract: Efficient rescue operations require a high level of situation awareness amongst decision‐makers and first responders for the purpose of achieving operations successfully and reducing losses. Moreover, a common operational picture between involved actors is required in order to support decision‐making. Therefore, different organisations and agencies have to collaborate, cooperate, and coordinate their actions with each other. Hence, effective interactions and communications between participants are vital to fulfil these essential needs. However, emergency actors still lack backing to exchange information effectively and ensure a common operational picture in order to reach shared situational awareness. For this reason, we aim to develop and implement Rescue MODES, a communication system oriented to support situation awareness amongst French emergency actors in rescue operations. In this paper, we examine and analyse actors' activities and interactions, so that the system will be based on the real needs of actors. We start by studying and modelling the communications, interactions, and information flow. This modelling is based on an application ontology. Then, we define requirements for good communication in these operations and present some existing systems in France and how each system responds to these requirements.